Uczta demonów: Orygenesa "Contra celsum" VIII 30 i Porfiriusza "De abstinentia" II 42-43 - Osek, Ewa (Vox Patrum, 2018)
The paper is to compare two parallel passages: Origen Contra Celsum VIII 30 and Porphyry De abstinentia II 42-43, which both concern meat-eating demonized as “demons’ feast”, and to inquire into a cause of this parallelism. The cause was a closest personal relationship between Origen and Porphyry in the years A.D. 244-249, as well as their indebtedness in a common source, hypothetically, Origen the Egyptian who published his treatise De daemonibus before A.D. 253.